THE ASSESSMENT OF PELAGIC FISH STOCK AND ITS DISTRIBUTIONS IN INDIAN OCEAN BY SPLIT BEAM ACOUSTIC SYSTEM - I NYOMAN ARNAYA (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2005)
The assessment of pelagic fish stock and its distribution in Indian Ocean, especially southern part of Java-Bali-Lombok, was conducted by SIMRAD EK-500 Split-beam Acoustic System, in October-November 2001. The research was carried out by R/V Baruna Jaya VII of Indonesia Institute of Science (LIPI), under the Fish Stock Assessment Project in Indonesian Waters of fiscal year 2001. As a result, it can be reported that (I) the dominant species of pelagic fish distributed in this area is small pelagic fish with target strength (TS) values between -54.00 dB to - 37.60 dB, absolute density of between 0.07 to 218 fish/1000 m\ and total fish stock of 526.570 ton/year; (2) the large pelagic fish (some species of tuna) also distributed in the area with average TS of -27 dB, absolute density between 0.00 to 0.07 fish/100 m\ and total fish stock of 386,260 ton/year. This result still needs more accurate verification, especially on the species composition and individual size of fish by a more appropriate biological sampling method (mid-water trawl). Consequently, more acoustical surveys combined with oceanographic sampling and exploratory fishing are needed to evaluate the existing condition of marine fish resources in the area, in order to optimize and set up the relevant and accurate fisheries management plan for suitable and responsible utilization offish resources. Keywords: Split-beam Acoustic System, Fish Stock Assessment, Target Strength, Density, Distribution, Indian Ocean (southern part of Java-Bali-Lombok).